The Potential Development of Safety Officers to Conduct in Accordance with Work Environment Regulations on Heat - Lertwisuttipaiboon, Sudaw; Sriopas, Apiradee; Suwanidcharoen, Sirirat; Chankong, Warangkana (Dhammathas Academic Journal, 2023)
The objectives of this research were: 1) to study the situation of heat problems of the establishments in Bangkok and metropolitan region; 2) to study the potential of safety officers on heat-related work; and 3) to analyze and propose the approaches for potential development of safety officers in accordance with work environment regulations on heat. The questionnaires and focus group discussion forms were used as research tools. A sample of 144 safety officers at professional level were randomly selected from the enterprises in Bangkok and the metropolitan region, and 12 key informants involved in thermal work safety were purposively selected for an online group discussion. Quantitative data were analyzed using descriptive statistics, and qualitative data were triangulated before analysis, synthesis, and conclusions. The results of study revealed that: 1. 36.11 % of enterprises had relatively high heat levels with an average Wet-bulb globe temperature (WBGT) 31–33 degrees Celsius, and 38.89 % of enterprises had heat-related health impacts or complaints of employees about 3-4 times per month. 2. The potential of safety officers with a high average score were the legally qualified personnel and heat stress monitors. The issue with a moderate average score was the ability to analyze the working conditions exposed to heat. 3. The approaches to developing potential for legal compliance consisted of 3 factors including legal factor, collaborative factor and management factor. This study suggests that the government agencies should develop legal compliance guidelines, support sustainable management systems and bilateral cooperation between employers and employees, as well as the use of heat control methods under the hierarchy of controls.